ANALISIS PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP KEMUNGKINAN FINANCIAL DISTRESS - Fauziah Nurul Fadhilah; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to examine the influence of corporate governance characteristics like ownership concentration, government ownership, managerial ownership, independent directors, managerial agency cost, and auditor’s opinion on probability of financial distress. Leverage, profitability, and liquidity used as control variable. The population in this study consists of all listed firms in Indonesia Stock Exchange in year 2010-2011. Sampling method used is purposive sampling. A criterion for firm with probability of financial distress is a company which is has a negative net income in a year ended. Data of these listed companies one and two years before they selected as samples. By omitting companies with some data unavailable, the samples consist of 296 companies. Then, there are 28 samples that included outlier should be excluded from samples of observation. So, the final amounts of the sample are 268 firms. Logistic regression used to be analysis technique. The empirical result of this study show that ownership concentration, managerial ownership, independent directors, and auditor’s opinion have negatively significant influenced on probability of financial distress. Managerial agency cost has positively significant and government ownership has no significant influence to probability of financial distress.